Assessment of primary school students' level of understanding the concepts of 2nd grade life sciences course based on different variables - Altintas, Gulsen; Savas, Behsat; Yesiltepe, Margrit (E D P SCIENCES, 2016)
The course of Life Sciences is one of the pivot courses taught in the first three years of primary school. Ensuring children get to know their environment and gain correct information related to their problems by making them investigate their natural and socio-cultural environment as well as providing them with necessary information, skills and behaviors for environmental adaptation are among the main purposes of Life Sciences course. The concepts to be instilled in students in line with these purposes are important. Since concepts are mostly intellectual and non-physical, they can only exist tangibly through examples. This study aims to assess Primary School Students' Level of Understanding the Concepts of 2nd Grade Life Sciences Course Based on Different Variables. 17 concepts included in the 2nd Grade Life Sciences course within the subject of School Excitement were addressed within the study, and students were requested to define and exemplify these concepts. A total of 102 students from five different primary schools of upper-middle and lower socioeconomic classes located in Manisa and Istanbul were included in the study in line with the intentional maximum diversity sample selection. The answers given by students for each concept were categorized and analyzed in terms of liking or disliking home, school, technology and the course of Life Sciences.
Keywords: Life sciences; concept; manner; Education & Educational Research